Muscle dysmorphia and mediating variables in physically active brazilian men (Revista Contexto & Saúde, 2026)
To assess whether muscularity dissatisfaction is a significant mediator between appearance ideal internalization and muscle dysmorphia symptoms in physically active Brazilian men. This is a cross-sectional study, which included 915 physically active Brazilian men aged 18 to 35, of any color, race, or ethnicity. Through an online survey, participants responded to a sociodemographic questionnaire, as well as measures to assess symptoms of muscle dysmorphia (Muscle Dysmorphic Disorder Inventory), appearance ideal internalization (Sociocultural Attitudes Toward Appearance Questionnaire-4), and muscularity dissatisfaction (Male Body Attitudes Scale - Revised). The correlation between variables was evaluated using Spearman’s correlation coefficient (rho), and a simple mediation analysis with bootstrapping of 5,000 resamples was conducted. Muscle dysmorphia symptoms showed a significant, positive correlation of moderate magnitude with appearance ideal internalization and a large magnitude with muscularity dissatisfaction. Muscularity dissatisfaction partially mediated (~50%) the relationship between appearance ideal internalization and muscle dysmorphia symptoms. Therefore, muscularity dissatisfaction represents an important mediator between appearance ideal internalization and muscle dysmorphia symptoms in physically active Brazilian men. These findings underscore the importance of interventions aimed at both reducing the appearance ideal internalization and addressing body dissatisfaction, thereby contributing to the prevention and treatment of muscle dysmorphia in this population.
Keywords: Body image; body dysmorphic disorders; men; mediation analysis